DEVELOPMENT OF A HYBRID LEARNING MODEL BASED ON THE OPEN BROADCASTER SOFTWARE (OBS) APPLICATION IN ECONOMICS SUBJECTS AT SMAIT HARAPAN MULIA PALEMBANG: NEEDS ANALYSIS - Nur Islamia; Makmum Raharjo; Santi Oktarina (JURNAL DARMA AGUNG, 2023)
The development of a hybrid learning model based on OBS is needed in a special learning of learning at a distance. This study aims to analyze the need for the development of an OBS-based hybrid learning model to improve student learning outcomes in economics subjects. This type of research is a survey research and a literature study as the basis and direction of this research. The instrument used was a needs analysis questionnaire with 25 questions given to 36 students of class X science and X social studies at SMAIT Harapan Mulia Palembang. In this study, data analysis used descriptive presntase. Based on the results of this study, students need an OBS-based hybrid learning model to improve learning outcomes in Economics subjects. Overall, this study implies that this learning model can improve student learning outcomes in Economics subjects. The application of the OBS-based hybrid learning model can be recommended for use in other subjects to gain effectiveness in learning activities